(untitled) (Global Journal of Science Frontier Research, 2013)
The aim of this paper is to introduce the concept of an intuitionistic M - fuzzy metric space with property ’E’ and prove common fixed point theorem for eight weakly compatible mappings in intuitionistic M - fuzzy metric space with property ’E’.